Comparison of Single Moving Average and Single Exponential Smoothing Methods in Estimating Jotun Brand Paint Inventory at Toko Cat Warna Baru - Hanim Setya Ningrum; Neni Mulyani; Hommy Dorothy Ellyany Sinaga (Budapest International Research and Critics University, 2022)
The research objective is to analyze comparison of single moving average and single exponential smoothing methods in estimating Jotun brand paint inventory at Toko Cat Warna Baru. This research uses qualitative research. This research is conducted at Toko Cat Warna Baru which is located at Jalan Sisingamangaraja Number 241, East Kisaran District, Asahan Regency. The data collection techniques used in this study used field research and library research. The framework in this research is problem identification, data collection, system analysis, system design, system implementation, and system testing. The results show that the lowest mean absolute percentage error error value in the single moving average method is 15.27% while the lowest mean absolute percentage error error value in the single exponential smoothing method is 12.11%. So, it can be concluded that the single exponential smoothing method is better than the single moving average method because it has a very small error value.